ANALISIS IMPLIKATUR METAFORA DAN ALIRAN FEMINISME MULTIKULTURAL PADA LIRIK LAGU “NALA” CIPTAAN TULUS (ANALYSIS OF METAPHOR IMPLICATURE AND MULTICULTURAL FEMINISM FLOWS ON THE LYRICS OF THE SONG "NALA" CREATED BY TULUS) - Tarigan, Dina Mariana Br (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractAnalysis of Metaphor Implicature and Multicultural Feminism Flows on the Lyrics of the Song "Nala" Created by Tulus. The lyrics of the song entitled "Nala" by Tulus tell about the love life of a character named Nala. Nala is the main character in the song lyrics by Tulus. Nala is a woman who lives a simple life and is strong in finding her soul mate. The story is written in song lyrics wrapped in linguistic style. The language style used in Nala's song lyrics is metaphorical implicatures of the type of love (serenada) and sadness (elegy). Through the use of metaphorical implicature, a multicultural feminist value can be found in the lyrics of Nala's song. The lyrics of the song Nala contain the meaning that injustice or discrimination against women occurs from the perspective of multicultural feminism. This research has two problem formulations, the first is to analyze the metaphorical implicatures contained in the lyrics of Tulus's song entitled "Nala" and the second is to analyze the flow of multicultural feminism contained in the lyrics of Tulus's song entitled "Nala". To analyze the data in this research, the author used a qualitative descriptive method. This research aims to determine the metaphorical implicature of the lyrics of Tulus' song entitled "Nala". Then, with this research, readers can find out that injustice is not only a matter of sex or gender, namely for women, but is also influenced by age, ethnicity, religion, appearance, education and economic factors. Multicultural feminism really upholds the value of diversity and culture. All humans should be treated equally and receive the same respect.Keywords: multicultural feminism, metaphorical implicature, song lyricsAbstrakAnalisis Implikatur Metafora dan Aliran Feminisme Multikultural pada Lirik Lagu “Nala” Ciptaan Tulus. Lirik lagu yang berjudul “Nala” karya Tulus menceritakan tentang kehidupan percintaan seorang tokoh yang bernama Nala. Nala adalah tokoh utama yang ada dalam lirik lagu karya Tulus. Nala merupakan seorang perempuan yang hidup sederhana dan tangguh dalam menemukan tambatan hati. Kisah itu ditulis dalam lirik lagu yang dibungkus melalui gaya bahasa. Gaya bahasa yang digunakan dalam lirik lagu Nala adalah implikatur metafora yang berjenis percintaan (serenada) dan kesedihan (elegi). Melalui penggunaan gaya bahasa implikatur metafora ditemukan sebuah nilai aliran feminisme multikultural pada lirik lagu Nala. Lirik lagu Nala mengandung makna bahwa terjadinya ketidakadilan atau diskriminasi terhadap perempuan dalam perspektif feminisme multikultural. Penelitian ini memiliki dua rumusan masalah, yang pertama adalah menganalisis implikatur metafora yang terdapat pada lirik lagu Tulus yang berjudul “Nala” dan yang kedua adalah menganalisis aliran feminism multikultural yang terdapat pada lirik lagu Tulus yang berjudul “Nala”. Untuk menganalisis data pada penelitian ini, penulis menggunakan metode deskriptif kualitatif. Penelitian ini bertujuan untuk mengetahui adanya implikatur metafora lirik lagu Tulus yang berjudul “Nala”. Kemudian dengan adanya penelitian ini, pembaca dapat mengetahui bahwa ketidakadilan bukan hanya persoalan jenis kelamin atau gender yaitu pada perempuan saja tetapi juga dipengaruhi oleh faktor usia, suku, agama, penampilan, pendidikan, dan ekonomi. Aliran feminisme multikultural sangat menjunjung tinggi nilai keberagaman dan kebudayaan. Sudah semestinya semua manusia harus diperlakukan setara dan mendapatkan penghargaan yang sama.Kata-kata kunci: feminisme multikultural, implikatur metafora, lirik lagu